1960
DOI: 10.1139/v60-123
|View full text |Cite
|
Sign up to set email alerts
|

The Decomposition of Methane by Low-Energy Electrons

Abstract: The decomposition of methane by a beam of electrons having energies between 15 and 100 ev has been studied using methane pressures between and mm of mercury. The products were frozen out on a surface cooled to about -220" C and situated approximately 5 millimeters from the electron beam.Ethane, ethylene, and acetylene were found to be the main products along with smaller amounts of saturated and unsaturated higher hydrocarbons. The results provide some evidence that under these experimental conditions ions do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1961
1961
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…These results were in agreement with previous corona discharge studies of gaseous methane in which basically saturated hydrocarbons were detected (Ponnamperuma and Pering, 1966;Ponnamperuma and Woeller, 1964;Ponnamperuma et al, 1969). Manton and Ticker (1960) have shown that when methane is irradiated with lowenergy electrons (<20 eV) and the products are protected from secondary degradation, the C 2 -hydrocarbon distribution is ethane > ethene > ethyne; as the energy of the electrons is raised to about 20 eV, the distribution is changed to ethane > ethene = ethyne, and at higher energies to ethane > ethyne > ethene. Based on these results, we inferred that the electron energy in our corona discharge experiments was very low (<20 eV).…”
Section: Resultssupporting
confidence: 93%
“…These results were in agreement with previous corona discharge studies of gaseous methane in which basically saturated hydrocarbons were detected (Ponnamperuma and Pering, 1966;Ponnamperuma and Woeller, 1964;Ponnamperuma et al, 1969). Manton and Ticker (1960) have shown that when methane is irradiated with lowenergy electrons (<20 eV) and the products are protected from secondary degradation, the C 2 -hydrocarbon distribution is ethane > ethene > ethyne; as the energy of the electrons is raised to about 20 eV, the distribution is changed to ethane > ethene = ethyne, and at higher energies to ethane > ethyne > ethene. Based on these results, we inferred that the electron energy in our corona discharge experiments was very low (<20 eV).…”
Section: Resultssupporting
confidence: 93%
“…The products found in these experiments are very similar to those found by Manton and Tickner (9) in their study of the decoinposition of methane by a beam of electrons. Since it is ltnown that the electrons in the negative regions of a d-c. glow discharge possess beam properties and have energies similar to those used in the electron beam experiments, this suggests that the products of the negative glow are formed by a inechanism siinilar to the one which they proposed.…”
Section: Discussionsupporting
confidence: 87%
“…Previous papers 2-5 on the radiolysis of pure methane show that sinall amounts of ethylene have been detected (G values from 0.05 to 0*12), as well as traces of iso-butene4 and isopentene.3~ 4 Acetylene and propylene have not been reported, althougb the former is a major product in gas discharge experiments,6, 7 and has recently been found 8 in methane passed at low pressures (10-2mmHg) through a beam of low-energy electrons.…”
mentioning
confidence: 95%